The Apartness of Ideal and Reality: Anticolonialism, Eurocentrism and Ubuntu Philosophy in the South African Freedom Charter - Poole, Max (Culture and History: Student Research Papers, 2022)
This article contributes to scholarly debate concerning universalist discourse, as either advantageous or detrimental to addressing inequalities between the West and the Global South. First, I explore the theoretical backdrop of the dispute, positing that differing notions of how multiple modernities interrelate informs divergent conceptualizations of universalist discourse, as either rigidly Eurocentric or contextually adaptable. Secondly, I analyze the South African Freedom Charter from both perspectives, arguing that we should recognize universalist discourse as a powerful tool in formulating political visions of decolonization; and conversely, that we should be cautious when utilizing such discourse due to its inherent Eurocentric capabilities.